2022
DOI: 10.3390/nu14061220
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Parkinson’s Disease

Abstract: Vitamin D is a fat-soluble secosteroid, traditionally considered a key regulator of bone metabolism, calcium and phosphorous homeostasis. Its action is made possible through the binding to the vitamin D receptor (VDR), after which it directly and indirectly modulates the expression of thousands of genes. Vitamin D is important for brain development, mature brain activity and associated with many neurological diseases, including Parkinson’s disease (PD). High frequency of vitamin D deficiency in patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 104 publications
0
29
0
Order By: Relevance
“…Studies on animal models and, more recently, on the human brain emphasize the role of vitamin D on neuroprotection. Recently, Pignolo et al [ 118 ] have extensively investigated the role of vitamin D in PD, describing its relevance in neuroprotection, its implication in all clinical aspects which characterize the disease, and suggesting a possible role of vitamin D supplementation as a possible therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on animal models and, more recently, on the human brain emphasize the role of vitamin D on neuroprotection. Recently, Pignolo et al [ 118 ] have extensively investigated the role of vitamin D in PD, describing its relevance in neuroprotection, its implication in all clinical aspects which characterize the disease, and suggesting a possible role of vitamin D supplementation as a possible therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D depletion is responsible for the death of dopaminergic neurons [ 118 ]. On the other hand, vitamin D supplementation protects against dopamine depletion in SNpc in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of vitamin D in the development and protection of neural cells has been described in a number of studies both in vitro and in vivo (1)(2)(3)(4). In parallel, over the past years, an increasing interest has emerged for the beneficial effects of vitamin D in neurodegenerative disorders, such as Parkinson's disease, Multiple sclerosis and Alzheimer's disease (AD) (5)(6)(7)(8)(9)(10)(11)(12)(13). Studies have concluded that there may be a close interaction between the molecular pathways of vitamin D mechanisms of action and the molecular pathways of AD pathology (14,15).…”
Section: Introductionmentioning
confidence: 99%